Traffic Management at Madhya Kailash Intersection along Rajiv Gandhi Road in Chennai - V, Sampathkumar.; Simron Rajkumar, Samuel (International Journal of Engineering and Technology, 2018)
This paper focuses on the improvement of the traffic flow at the three-major congested intersection located near Madhya Kailash, Tidel Park and SRP Tools along Rajiv Gandhi road in Chennai City. Road inventory survey and volume count survey have been conducted at the three intersections. Volume accumulation curves are developed to obtain the peak volume and peak time. From the analysis it is found that the peak volume is about 2321 passenger car equivalence (PCE), 2544 PCE and 2396 PCE at the three intersections respectively during peak hour. The volume to capacity ratio is about 1.29, 1.41 and 1.33 obtained which makes high level of congestion and poor level of service in turn shows an immediate need of traffic management measure. Transport system management concepts are suggested to manage the traffic flow which will improve the flow at the study intersections.Â Â